Market competition, lean manufacturing practices and the role of Management Accounting Systems (MAS) information - Ismail, Kamisah; Isa, Che Ruhana; Mia, Lokman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Adoption of advanced manufacturing techniques such as lean manufacturing is one of the strategies that help manufacturing firms to sustain their competitiveness and achieve the desired outcomes. It is argued that the traditional Management Accounting Systems (MAS) are no longer capable of providing information necessary to operate in the ever changing business environment. This study examines the role of MAS information in the relationship between market competition, lean manufacturing and organisational performance. Data were gathered using a questionnaire survey from manufacturing firms listed in the Federation of Malaysian Manufacturers (FMM) Directory. The results reveal the relationships between lean manufacturing and the MAS, as well as between the MAS and performance, are positive and significant, which suggest that the relationship between lean manufacturing and performance is indirect through the MAS. This provides evidence that the use of MAS information in a lean manufacturing environment facilitates firms in improving organisational performance.